2010
DOI: 10.1002/mrc.2614
|View full text |Cite
|
Sign up to set email alerts
|

Trivinylphosphine and trivinylphosphine chalcogenides: stereochemical trends of 31P1H spin-spin coupling constants

Abstract: A combined theoretical and experimental study of the stereochemical behavior of (31)P-(1)H spin-spin coupling constants has been performed in the series of trivinylphosphine and related trivinylphosphine oxide, sulfide and selenide. Theoretical energy-based conformational analysis of the title compounds performed at the MP2/6-311G** level reveals that each of the four compounds of this series exists in the equilibrium mixture of five true-minimum conformers, namely s-cis-s-cis-s-cis, s-cis-s-cis-gauche, syn-s-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
(9 reference statements)
2
20
0
Order By: Relevance
“…Relative energies are given in parentheses (kJ/mol), dihedral angles are shown on structures. Reproduced from Fedorov et al with the permission of John Wiley and Sons…”
Section: Computation Of Spin–spin Coupling Constants Involving Phosphmentioning
confidence: 77%
See 4 more Smart Citations
“…Relative energies are given in parentheses (kJ/mol), dihedral angles are shown on structures. Reproduced from Fedorov et al with the permission of John Wiley and Sons…”
Section: Computation Of Spin–spin Coupling Constants Involving Phosphmentioning
confidence: 77%
“…In two related publications by Fedorov et al dealing with the calculation of geminal and vicinal phosphorus‐proton coupling constants, 2 J PH and 3 J PH , in trivinyl phosphine ( 1 ) and trivinyl phosphine chalcogenides ( 2 ‐ 4 ), it was found that each of the four compounds of this series existed in the equilibrium mixture of five true‐minimum conformers, namely, s‐cis‐s‐cis‐s‐cis , s‐cis‐s‐cis‐gauche , syn‐s‐cis‐gauche‐gauche , anti‐s‐cis‐gauche‐gauche , and gauche‐gauche‐gauche .…”
Section: Computation Of Spin–spin Coupling Constants Involving Phosphmentioning
confidence: 99%
See 3 more Smart Citations